Valve material and preparation method and application thereof

CN119730888APending Publication Date: 2025-03-28VENUS MEDTECH (HANGZHOU) INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380059010.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-22
Filing Date
2023-07-12
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Polymer valve materials are prone to creep and edge tearing during use, which affects the fluid performance and service life of the valve.

Method used

Polyurethane A and polyurethane B are used as the skeleton and composite layer materials, and a grid-like structure is formed through electrospinning. Combined with hot pressing treatment and plasma surface treatment, the valve's creep resistance and tear resistance are improved.

Benefits of technology

Significantly improves the valve's creep resistance and edge tear resistance, extending the valve's service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730888A_ABST
    Figure CN119730888A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer valve material, which comprises: a skeleton, which is formed by using polyurethane A as a raw material and through electrostatic spinning; and the composite layer adopts polyurethane B as a raw material and is compounded on the framework. The invention also discloses a preparation method of the polymer valve material, which comprises the following steps: a spinning step: carrying out electrostatic spinning on a polyurethane A solution to obtain a prefabricated film; and a compounding step: compounding polyurethane B and the prefabricated film to obtain the polymer valve material, and an adjusting step: carrying out hot pressing treatment on the prefabricated film before or in the compounding process. The valve leaflet material prepared by the invention can improve the creep resistance and edge tear resistance of the valve leaflet and prolong the service life of the valve.
Need to check novelty before this filing date? Find Prior Art

Description

Valve material, preparation method and application thereof Technical Field

[0001] The present application relates to the technical field of interventional materials, and in particular to a valve material, a preparation method thereof, and an application thereof. Background Art

[0002] The human heart is divided into four chambers: the left atrium, left ventricle, right atrium, and right ventricle. Each atrium connects to the two ventricles, which in turn connect to the two aortas. Heart valves function as one-way valves between the atria and ventricles, and between the ventricles and aortas. The four valves in the human body are the mitral valve, tricuspid valve, aortic valve, and pulmonary valve.

[0003] Valvular heart disease is a heart condition caused by narrowing or / and insufficiency of the heart valves due to various reasons. Under normal circumstances, open heart valves allow blood to flow forward, while closed heart valves prevent blood from flowing back, thus ensuring unidirectional blood flow within the heart. When the valves are narrow, the pressure load on the heart chambers increases. When the valves are insufficiency, the volume load on the heart chambers increases. These hemodynamic changes can lead to structural changes and functional abnormalities in the atria or ventricles, ultimately resulting in clinical manifestations such as heart failure and arrhythmias.

[0004] A prosthetic heart valve (CVP) is an implantable replacement for a heart valve (aortic, tricuspid, or mitral), enabling unidirectional blood flow and reproducing the functions of a natural heart valve. When a heart valve is severely damaged and valve separation or repair surgery cannot restore or improve valve function, a CVP is used.

[0005] Artificial heart valves are generally divided into mechanical and bioprosthetic valves. Mechanical valves are made entirely of artificial materials, while bioprosthetic valves are made of biological materials. Pericardial materials have good biocompatibility and have long been used in surgical and interventional valves. However, material sources are limited, and material uniformity is poor, requiring extensive labor for screening, resulting in low utilization rates and high costs. Currently, polymer valves are receiving extensive research due to their ease of processing, uniform thickness, and performance. Currently, the main polymer materials used for valve leaflets include polyurethane and polyetheretherketone. For example, the polyurethane preparation methods disclosed by Foldax, RUA Structural Heart, Triskele-UCL, and DSM can be used to prepare polyurethane materials for medical devices such as implants, heart valves, and drug delivery devices. These materials have been widely used in the development of implantable medical devices. For example, the literature (Loshini S. Dandeniyage, Development of high-strength siloxane poly(urethane-urea) elastomers based on linked macrodiols for heart valve application, Society for Biomaterials, 2017) demonstrates that the prepared materials have good biocompatibility and are very suitable for use in valve leaflet materials. However, polymer materials are prone to creep, and the leaflets easily extend and deform during use, affecting the valve's fluid flow performance. In addition, they have poor edge tear strength and are prone to cracking. This is one of the main issues limiting the development of polymer valves.

[0006] Summary of the Invention

[0007] The present application provides a method for preparing a polymer valve material, which improves the creep resistance and edge tear resistance of the valve leaflets and extends the service life of the valve.

[0008] A polymer valve material, comprising:

[0009] The skeleton is formed by electrospinning using polyurethane A as a raw material;

[0010] The composite layer uses polyurethane B as a raw material and is composited onto the skeleton.

[0011] The skeleton has a grid-like structure, and the polyurethane B fully infiltrates into the skeleton, eventually filling the grid of the skeleton and being compounded on the surface of the skeleton.

[0012] Optionally, the melting point of polyurethane A is higher than the melting point of polyurethane B and the difference is at least 30°C.

[0013] Optionally, the polyurethane A has a melting point of 180-300° C.; further, the Shore hardness of the polyurethane A is 50D-90D; and the number average molecular weight of the polyurethane A is greater than 50,000.

[0014] Optionally, the melting point of the polyurethane B is 100-240° C.; further, the Shore hardness of the polyurethane B is 50A-80A; and the number average molecular weight of the polyurethane B is greater than 35,000.

[0015] That is, preferably, the melting point of polyurethane A is at least 30°C higher than that of polyurethane B. Further preferably, when this condition is met, the melting point of polyurethane A is 180-300°C, and the melting point of polyurethane B is 100-240°C.

[0016] Optionally, the thickness of the skeleton is 0.1 mm to 1 mm.

[0017] Optionally, the porosity of the skeleton is 65% to 90%.

[0018] Optionally, the thickness of the composite layer is 0.05 mm to 0.5 mm.

[0019] Optionally, the raw materials for electrospinning the skeleton also include a core material, and the core material is coaxially electrospun with the polyurethane A to form the skeleton. That is, in this solution, polyurethane A and the core material are used as raw materials and the skeleton is formed by coaxial electrospinning.

[0020] The strength of the core material raw material needs to be higher than that of polyurethane A to enhance the comprehensive strength of the skeleton fiber filaments. The fiber filaments in the skeleton formed by coaxial electrospinning include a core material located at the axis and an outer layer of polyurethane A wrapped around the core material.

[0021] Optionally, when polyurethane A meets the conditions mentioned above, the core material is made of polyamide PA or polyethylene PE.

[0022] A method for preparing a polymer valve material, comprising:

[0023] Spinning step, electrospinning the polyurethane A solution to obtain a prefabricated membrane;

[0024] a compounding step of compounding polyurethane B with the prefabricated film to obtain the polymer valve material;

[0025] The adjustment step is to perform a hot pressing treatment on the prefabricated membrane before or during the compounding process.

[0026] The selection of polyurethane A and polyurethane B and their relationship have been described above and will not be repeated here.

[0027] Optionally, the mass percentage concentration of the polyurethane A solution is 8% to 18%; the solvent is V THF / V DMF 1:1 to 5:1 mixed solvent. THF (tetrahydrofuran).

[0028] Specifically, high temperature resistant polyurethane A (high hard segment content) in (V THF / V DMF The polyurethane A solution is stirred for 4 to 16 hours to prepare an 8% to 18% (wt.%) uniform solution.

[0029] Optionally, the polyurethane material A can be purchased directly from commercially available known commodities;

[0030] Optionally, the polyurethane material A can be prepared by a currently disclosed common polyurethane material synthesis method, such as the synthesis methods of polyurethane materials used in implantable devices disclosed by Foldax, RUA Structural Heart, Triskele-UCL, DSM, etc. Preferably, the synthesis method described in the literature (Loshini S. Dandeniyage, Development of high strength siloxane poly(urethane-urea) elastomers based on linked macrodiols for heart valve application, Society For Biomaterials, 2017) can be directly used to prepare polyurethane materials with different soft and hard segment contents.

[0031] Optionally, the electrospinning conditions are controlled as follows: humidity 45-55%, voltage 10-25 KV, propulsion speed 0.5-1 mL / h, spinning distance 15-25 cm, and needle size 10G-30G.

[0032] Optionally, during the spinning step, the polyurethane A solution and the core material solution are coaxially electrospun to form a prefabricated membrane. This preferred embodiment of adding a core material produces a fiber with a higher strength polymer material inside, which can reduce stress concentration at the interface between the fiber and the matrix material (polyurethane B), further improving the creep resistance and tear strength of the material; at the same time, the outer layer of the fiber is more compatible with the outer layer matrix material (polyurethane B).

[0033] Optionally, the core material solution is a polyamide PA solution or a polyethylene PE solution, with a mass percentage concentration of 3% to 10%; the solvent can be N,N-dimethylformamide (DMF).

[0034] In a specific scheme for preparing the core material PA or PE solution, a certain mass of polyamide (molecular weight 15,000 to 30,000) or polyethylene (molecular weight above 1,000,000) is weighed and dissolved in N,N-dimethylformamide (DMF), stirred for 4 to 16 hours to fully dissolve, and a uniform solution with a mass concentration of 3% to 10% is prepared, which is then allowed to stand for use.

[0035] Optionally, the ratio of the core material solution to the polyurethane A solution is calculated based on a mass ratio of the core material PA or PE to the polyurethane A of 5:1 to 1:5.

[0036] Optionally, the method further comprises the step of removing residual solvent from the obtained prefabricated membrane; for example, the prefabricated membrane may be vacuum-dried at room temperature to achieve the purpose of removing residual solvent.

[0037] Optionally, the prefabricated membrane has a thickness of 0.1 to 1 mm.

[0038] Optionally, the porosity of the prefabricated membrane is 65% to 90%.

[0039] Optionally, the prefabricated membrane is subjected to hot pressing before lamination: the prefabricated membrane is dipped in a polyurethane B solution or a polyurethane B prepolymer solution after the hot pressing treatment.

[0040] Optionally, the temperature of the hot pressing treatment is 100 to 240° C., and the time of the hot pressing treatment is 5 minutes to 2 hours.

[0041] Optionally, the thickness of the prefabricated membrane after hot pressing is 0.05 to 0.5 mm.

[0042] For dip coating in polyurethane B solution:

[0043] Optionally, one implementation method of the dip coating is: immersing the prefabricated membrane after the heat pressing treatment in the polyurethane B solution for 4 to 60 seconds and then quickly taking it out, which can be repeated.

[0044] Optionally, the mass percentage concentration of the polyurethane B solution is 20% to 30%.

[0045] During the dip-coating process, the pre-polymer film made from polyurethane A serves as the material backbone, while polyurethane B serves as the composite layer. Polyurethane A and polyurethane B have different solubility requirements. As a general rule, the solvent system used in the dip-coating step must ensure that polyurethane B dissolves well while the pre-polymer film made from polyurethane A maintains the integrity of its backbone. For example, DMF or DMAc can be used.

[0046] Specifically, a certain amount of polyurethane B is dissolved in DMF or DMAc at 60-90° C. under a nitrogen atmosphere and stirred for 4-16 hours to fully dissolve into a 20 wt % to 30 wt % solution.

[0047] Optionally, the polyurethane material B can be directly purchased from known commercial products;

[0048] Optionally, the polyurethane material B can be prepared by a currently disclosed common polyurethane material synthesis method, such as the synthesis methods of polyurethane materials used in implantable devices disclosed by Foldax, RUA Structural Heart, Triskele-UCL, DSM, etc. Preferably, the synthesis method described in the literature (Loshini S. Dandeniyage, Development of high strength siloxane poly(urethane-urea) elastomers based on linked macrodiols for heart valve application, Society For Biomaterials, 2017) can be directly used to prepare polyurethane materials with different soft and hard segment contents.

[0049] In this application, there is no clear limit on the number of times the prepolymer film is dipped in the polyurethane B solution, as long as the required thickness is achieved. Optionally, 1 to 3 dips are generally sufficient to achieve the required thickness.

[0050] For dip coating in polyurethane B prepolymer:

[0051] Optionally, the polyurethane B prepolymer is synthesized by: conducting a prepolymerization reaction between polymer diol and isocyanate under a nitrogen atmosphere; after the prepolymerization reaction is completed, the system is cooled to room temperature, a diol small molecule chain extender is added and stirred evenly to obtain the polyurethane B prepolymer.

[0052] Optionally, one implementation method of the dip coating is: immersing the prefabricated membrane after the heat pressing treatment in the polyurethane B prepolymer, and heating it in an oven to perform further chain extension reaction.

[0053] Optionally, the heating in the oven is carried out in an oxygen-free environment, such as in a nitrogen atmosphere, with a heating temperature of 60 to 100° C. and a heating time of 3 to 8 hours.

[0054] Optionally, a hot pressing treatment is performed during the compounding step: the prefabricated film and polyurethane B particles are placed in a hot pressing mold, the hot pressing mold is heated to melt the polyurethane B particles while the prefabricated film is not melted, and the melted polyurethane B fully infiltrates into the prefabricated film.

[0055] Optionally, the mass ratio of the prefabricated film to polyurethane B is 1:3 to 3:1.

[0056] The temperature and duration of the hot pressing treatment are preferably such that the polyurethane B particles are completely melted while the pre-film remains unmelted. Optionally, the temperature of the hot pressing treatment is 100 to 240° C., and the duration of the hot pressing treatment is 5 minutes to 2 hours. Within this parameter range, the condition of “the polyurethane B particles are completely melted while the pre-film remains unmelted” is met.

[0057] Optionally, the method further includes: performing surface treatment on the polymer valve material obtained in the compounding step; further, the surface treatment is: performing plasma treatment on the polymer valve material.

[0058] Optionally, the conditions for the plasma treatment are: using SO2, CO2, NH3 or O2 as the reaction gas, the power is 100-250W, and the treatment time is 5-15 minutes.

[0059] Specifically, the obtained polymer film is placed in an inverse plasma discharge machine, SO2 / CO2 / NH3 / O2 is used as the reaction gas, the power is 100-250W, and the treatment is carried out for 5-15 minutes to obtain a plasma-treated polymer film.

[0060] Optionally, the method further includes: cutting the polymer valve material after plasma treatment into leaflet shapes.

[0061] The present application also provides a polymer valve material prepared by the method described.

[0062] The polymer leaflet material of the present application can be used for interventional artificial heart valves, such as through minimally invasive intervention, and can also be used for surgical artificial heart valves, such as through surgical implantation.

[0063] The present application also provides an artificial valve, comprising a stent and a valve material sewn onto the stent. The valve material is the polymer valve material described in the present application.

[0064] Optionally, the artificial valve is an artificial heart valve.

[0065] Compared with the prior art, this application has at least one of the following beneficial effects:

[0066] (1) Good creep resistance;

[0067] (2) Strong edge tear resistance;

[0068] (3) The service life of the valve is extended. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] FIG1 is a surface SEM image of the electrospun preformed membrane in Example 1.

[0070] FIG2 is a surface SEM image of the composite membrane material in Example 1.

[0071] FIG3 is a cross-sectional SEM image of the composite membrane material in Example 1.

[0072] FIG4 is a graph showing the elastic deformation change of the pure polyurethane material and the composite film material with the number of cycles in Example 1.

[0073] FIG5 is a TEM image of the coaxial electrospinning membrane material in Example 3.

[0074] FIG6 is a quantitative comparison of platelet adhesion of the surface-modified and non-surface-modified composite membranes in Example 5.

[0075] FIG7 is a comparison of contact angles of the surface-modified and non-surface-modified composite films in Example 5. DETAILED DESCRIPTION

[0076] The following will be combined with the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the embodiments described are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

[0077] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application pertains. The terms used herein in the specification of this application are for the purpose of describing specific embodiments only and are not intended to limit this application.

[0078] Polymer leaflet materials are prone to creep, and the leaflets are prone to elongation and deformation during use, affecting the fluid performance of the valve. In addition, the edge tear strength is poor and cracking is prone to occur. These problems limit the development of polymer valves.

[0079] This application addresses the creep and edge tearing issues associated with polymer materials. It proposes incorporating a nano- or micron-sized fiber mesh into the polymer material, then forming the material into a single piece to create a polymer membrane with a fiber mesh. This approach aims to enhance the mechanical properties of the membrane by incorporating the fiber mesh, while also improving interfacial bonding strength through the infiltration and filling of the nanofiber mesh, thereby enhancing the membrane's creep and tear resistance.

[0080] In order to solve the above problems, this application provides a polymer valve material on the one hand, which includes a skeleton and a composite layer. The skeleton is a nano or micro fiber mesh, which uses polyurethane A as raw material and is formed by electrospinning; the composite layer uses polyurethane B as raw material and is composited to the skeleton.

[0081] The skeleton has a grid-like structure, and the polyurethane B fully infiltrates the skeleton, ultimately filling the grid and forming a composite layer on the skeleton's surface. The thickness of the electrospun skeleton can be controlled within 0.1mm to 1mm, and the porosity can be controlled within 65% to 90%. The thickness of the composite layer attached to the skeleton through various methods can be controlled within 0.05mm to 0.5mm.

[0082] The polymer valve material as described above can be prepared by the improved preparation method of the present application, which includes a spinning step, a compounding step and an adjustment step. In the spinning step, the polyurethane A solution is electrospun to obtain a prefabricated membrane; in the compounding step, the polyurethane B is compounded with the prefabricated membrane obtained in the spinning step; and the adjustment step is to perform hot pressing on the obtained prefabricated membrane before or during compounding.

[0083] First, a prefabricated membrane is prepared through a spinning step as a skeleton structure, and then polyurethane B is compounded to the skeleton and subjected to hot pressing treatment before or during compounding, thereby eliminating the obvious interface between the polymer material and the fiber mesh and improving the bonding strength between the two.

[0084] In this application, polyurethanes with different melting points are selected as the skeleton material and the composite layer, respectively. The melting point of polyurethane A is higher than that of polyurethane B. The prefabricated membrane prepared from polyurethane A maintains the integrity of its skeleton structure when composited with polyurethane B. Preferably, the melting point of polyurethane A is at least 30°C higher than that of polyurethane B. Furthermore, preferably, polyurethane A has a melting point between 180°C and 300°C, and polyurethane B has a melting point between 100°C and 240°C.

[0085] The polyurethane A that meets the requirements of the melting point, hardness and molecular weight of this application can be synthesized by itself or purchased as a commercial product that meets the corresponding parameters.

[0086] The polyurethane B that meets the melting point, hardness and molecular weight requirements of this application can be synthesized by itself, or purchased from the market, or the polyurethane B precursor, i.e., the polyurethane B prepolymer, can be synthesized by itself first.

[0087] As a specific synthesis method of polyurethane B prepolymer:

[0088] 1) Under a nitrogen atmosphere, PTMO (1000 g / mol, 10 g) and PDMS (1000 g / mol, 50 g) (PTMO to PDMS molar ratio of 1:5, total mass 60 g) were added to MDI (29.375 g) with stirring at 80°C. The reaction was allowed to proceed for 4 h, and 8.02 g of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane (BHTD) was added dropwise for prepolymerization. The system was then cooled to room temperature, and 2.59 g of 1,4-butanediol (BDO) (BHTD:BDO molar ratio of 1:1) was added and stirred for 30 min. 2) The prepolymer was stored under a nitrogen atmosphere for 24 h to obtain a polyurethane prepolymer B solution.

[0089] In the electrospinning step, the polyurethane A solution is made into a prefabricated membrane by electrospinning. Based on the preparation of the prefabricated membrane by electrospinning, this application selects a polymer material with higher strength as the internal structure of the fiber filament, that is, the polyurethane A solution is used as the shell solution and coaxially electrospun with the core material solution. The core material solution selects a polyamide PA or polyethylene PE solution with higher strength.

[0090] For the conditioning step involving pre-compounding hot pressing, the pre-spun membrane is first hot pressed. The pre-spun membrane is then dip-coated in a polyurethane B solution or polyurethane B prepolymer. In this embodiment, the hot pressing temperature is preferably 125-180°C, and the hot pressing time is preferably 5 minutes to 2 hours.

[0091] In one embodiment of the dip coating treatment in polyurethane B solution, a certain amount of polyurethane B is dissolved in DMF or DMAc under a nitrogen atmosphere at 60-90°C and stirred for 4-16 hours to fully dissolve into a 20wt%-30wt% solution; the prefabricated membrane after the hot pressing treatment is immersed in the polyurethane B solution for 4-60 seconds and then quickly removed, which can be repeated.

[0092] In one embodiment of the dip coating treatment in polyurethane B prepolymer, polyurethane B prepolymer needs to be prepared first, and the prefabricated film after the heat pressing treatment is immersed in the polyurethane B prepolymer, and heated in an oven to further perform a chain extension reaction.

[0093] In the scheme of hot pressing before lamination and combining it with prepolymer dip coating of polyurethane B, hot pressing before lamination can enhance the strength of the prefabricated membrane, but it will also respond to compressing the pores of the prefabricated membrane. However, when polyurethane B is dip-coated in the form of a prepolymer, the prepolymer has a low molecular weight and short chain segments. Compared with high-molecular-weight polyurethane, the prepolymer is more easily incorporated into the fiber skeleton formed by polyurethane A during the dip coating process, resulting in better system integration and more complete molecular motion. Chain extension polymerization is then further completed during the drying process. This prepolymer dip coating scheme can, on the one hand, lengthen the chain length of polyurethane B, and on the other hand, the polymerization of some polyurethane occurs between molecules within the electrospun membrane fibers, thus further eliminating the interface and improving compatibility. This improves the overall strength of the composite membrane while also ensuring better interfacial bonding of the composite membrane.

[0094] In the scheme where the conditioning step involves hot pressing during compounding, the preformed membrane and polyurethane B particles from the spinning step are placed in a hot pressing mold. The mold is heated until the polyurethane B particles melt while the preformed membrane remains unmelted. The melted polyurethane B fully infiltrates the preformed membrane, and then hot pressing is performed to produce the composite valve material. The temperature and duration of the hot pressing process are preferably such that the polyurethane B particles completely melt while the preformed membrane remains unmelted. In one alternative, the hot pressing process temperature is 100-240°C, and the hot pressing process time is 5 minutes to 2 hours.

[0095] In the scheme of hot pressing during the composite process, the prefabricated membrane is relatively thicker and has larger pores, polyurethane B is easier to infiltrate, and the interface bonding of the composite membrane is better. At the same time, hot pressing during the composite process can also improve the overall strength of the composite membrane. The composite membrane prepared by this scheme has both better strength and interface bonding.

[0096] To further improve the biocompatibility of the valve material, the composite material was surface treated. A preferred surface treatment method involves using plasma technology. In one specific embodiment, the resulting polymer film is placed in a reverse plasma discharger using SO2 / CO2 / NH3 / O2 as the reaction gases at a power of 100-250W for 5-15 minutes to obtain a plasma-treated polymer film. Experiments have demonstrated that this surface-treated polymer film exhibits excellent platelet resistance.

[0097] The following is described with specific examples:

[0098] Example 1

[0099] (1) High temperature resistant polyurethane A (melting point 195℃, Shore hardness 80D) in solvent (V THF / V DMF The mixture was stirred for 4 h to prepare a 10% (wt.%) uniform solution, which was a polyurethane A solution.

[0100] Under a nitrogen atmosphere, PTMO (1000 g / mol, 10 g) was added to MDI (9.97 g) with stirring at 80°C for 2 h. 1.35 g of 1,4-butanediol (BDO) was added dropwise for chain extension reaction. The reaction was continued for 2 h. The system was then cooled to room temperature, and 0.90 g of ethylenediamine (EDA) (BDO:EDA molar ratio of 1:1) was added dropwise for 4 h to obtain polyurethane A.

[0101] (2) The obtained polyurethane A solution was electrospun under the conditions of humidity of 50%, voltage of 15 kV, propulsion speed of 1 mL / h, spinning distance of 20 cm and needle type of 21G to obtain a prefabricated membrane with a thickness of 0.8 to 1 mm.

[0102] (3) The prefabricated membrane was vacuum dried at room temperature for 48 h to remove the residual solvent.

[0103] (4) The prefabricated membrane after removing the residual solvent is subjected to hot pressing treatment: the hot pressing temperature is 170° C., the hot pressing time is 10 min, and the thickness of the prefabricated membrane after the hot pressing treatment is 0.08 to 0.12 mm.

[0104] (5) A certain amount of polyurethane B (melting point 160° C., Shore hardness 80A) was dissolved in DMF at 80° C. under nitrogen atmosphere and stirred for 4 h until it was fully dissolved to a 10% (wt.%) solution.

[0105] Under nitrogen atmosphere, PTMO (1000 g / mol, 10 g) and PDMS (1000 g / mol, 50 g) (PTMO to PDMS mass ratio of 1:5, total mass 60 g) were added to MDI (29.375 g) with stirring at 80°C and reacted for 4 h. 8.02 g of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane (BHTD) was added dropwise for chain extension reaction and reacted for 2 h. Subsequently, 2.59 g of 1,4-butanediol (BDO) (BHTD:BDO molar ratio of 1:1) was added and reacted for 4 h to obtain polyurethane B.

[0106] (6) Immerse the prefabricated membrane after the hot pressing treatment in step (4) in the polyurethane B solution prepared in step (5) and quickly take it out (immerse for 4 to 6 seconds), and dry it in a nitrogen atmosphere at 60 to 80° C. for 24 hours to form a polymer membrane with a reinforced network structure in the middle, and the membrane thickness is 0.15 mm.

[0107] The surface SEM image of the electrospun preformed membrane material prepared in steps (1) to (3) of Example 1 is shown in Figure 1; the surface SEM images and cross-sectional SEM images of the composite membrane material after treatment in steps (4) to (6) are shown in Figures 2 and 3. As shown in Figures 2 and 3, the fiber mesh is wrapped by the solution and there is no obvious interfacial delamination, indicating that this step improves the bonding strength between the fiber mesh and the polyurethane material.

[0108] According to ATSM D412 and ATSM D624, the mechanical properties of polyurethane B films (polyurethane B is formed by conventional methods, such as pouring a polyurethane B solution into a flat mold and allowing the solvent to evaporate) and composite films were measured. The test results are shown in Table 1:

[0109] Table 1

[0110] Compared to polyurethane B membrane, the composite membrane formed by adding an electrospun fiber mesh to the polyurethane material helps improve the mechanical strength and edge tear resistance of the valve leaflets. Hot pressing also controls the thickness of the electrospun membrane.

[0111] A single-load test examined the creep properties of the material: At room temperature, a creep test was conducted with an applied stress of 2 MPa. The test frequency was set at 1 Hz, and 36,000 cycles were performed. The elastic deformation at different cycle numbers was measured. The test results are shown in Figure 4. Compared to polyurethane B, the composite film maintained a stable elastic deformation of 10% after 36,000 cycles, demonstrating its excellent creep resistance.

[0112] Example 2

[0113] (1) High temperature resistant polyurethane A (melting point 195°C, Shore hardness 80D, same as Example 1) THF / V DMF The mixture was stirred for 4 h in a 1:1) solution to prepare a 10% (wt.%) uniform solution, which was a polyurethane A solution.

[0114] (2) The obtained polyurethane A solution was electrospun under the conditions of humidity of 50%, voltage of 15 kV, propulsion speed of 1 mL / h, spinning distance of 20 cm and needle type of 21G to obtain a prefabricated membrane with a thickness of 0.8 to 1 mm.

[0115] (3) The prefabricated membrane was vacuum dried at room temperature for 48 h to remove the residual solvent.

[0116] (4) The prefabricated membrane after removing the residual solvent is subjected to hot pressing treatment. The hot pressing temperature is 170° C. and the hot pressing time is 10 min. The thickness of the prefabricated membrane after the hot pressing treatment is 0.10 mm.

[0117] (5) Prepare polyurethane B prepolymer:

[0118] 1) Under nitrogen atmosphere, PTMO (1000 g / mol, 10 g) and PDMS (1000 g / mol, 50 g) (PTMO to PDMS molar ratio of 1:5, total mass 60 g) were added dropwise to MDI (29.375 g) with stirring at 80°C for 4 h. 8.02 g of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane (BHTD) was added dropwise for chain extension. The system was then cooled to room temperature, and 2.59 g of 1,4-butanediol (BDO) (BHTD:BDO molar ratio of 1:1) was added and stirred for 30 min.

[0119] 2) The prepolymer needs to be stored under a nitrogen atmosphere for 24 hours to obtain polyurethane B prepolymer.

[0120] (6) Immerse the prefabricated membrane after the hot pressing treatment in step (4) in the polyurethane B prepolymer in step (5) and quickly take it out (4 to 6 seconds), react in an oven at 80°C in a nitrogen atmosphere for 4 hours, and then dry it at 60°C for 24 hours to obtain a composite membrane with a membrane thickness of 0.15 mm.

[0121] According to ATSM D412 and ATSM D624, the mechanical properties of polyurethane B films (polyurethane B is formed by conventional methods, such as pouring a polyurethane B solution into a flat mold and allowing the solvent to evaporate) and composite films were measured. The test results are shown in Table 2:

[0122] Table 2

[0123] Example 3

[0124] (1) High temperature resistant polyurethane A (melting point 195°C, Shore hardness 80D, same as Example 1) THF / V DMF The mixture was stirred for 4 h in a 1:1) solution to prepare a 10% (wt.%) uniform solution, which was the polyurethane A solution and was used as the shell solution.

[0125] (2) Weigh a certain amount of high molecular weight polyethylene (molecular weight 1.5 million) and dissolve it in N,N-dimethylformamide (DMF) solution. Stir for 8 hours until it is fully dissolved and a uniform solution with a mass concentration of 10% (wt.%) is prepared as the core solution. Let it stand for use.

[0126] (3) Coaxial electrospinning of the core solution and the shell solution (the core solution and the shell solution were calculated in a polyethylene to polyurethane A mass ratio of 1:1) to obtain a prefabricated membrane with a thickness of 0.8 to 1 mm. Electrospinning parameters included: 50% humidity, 15 kV voltage, 1 mL / h propulsion speed, 25 cm spinning distance, and a 17G to 22G needle.

[0127] (4) The prefabricated membrane was vacuum dried at room temperature for 48 h to remove the residual solvent.

[0128] (5) The prefabricated composite film treated in step (4) is placed in a hot pressing mold, and polyurethane B particles (melting point of 160°C, Shore hardness of 80A, polyurethane B particles are the same as in Example 1, and the mass ratio of the prefabricated film to the polyurethane B particles is 1:1) are added to the hot pressing mold. The hot pressing mold is heated at a temperature of 170°C for 10 minutes to completely melt the polyurethane B and leave the prefabricated composite film unmelted.

[0129] (6) The molten polyurethane B is fully infiltrated into the prefabricated composite membrane and then molded into an integral body, forming a polymer membrane with a reinforced mesh structure in the middle part, with a thickness of 0.15 mm. The fiber spinning that constitutes the mesh structure itself has a filamentous structure of a polymer material with higher strength selected inside.

[0130] The TEM image of the coaxial electrospinning prefabricated membrane material prepared in steps (1) to (4) in Example 3 is shown in FIG5 .

[0131] According to ATSM D412 and ATSM D624, the mechanical properties of polyurethane B films (polyurethane B is formed by conventional methods, such as pouring a polyurethane B solution into a flat mold and allowing the solvent to evaporate) and composite films were measured. The test results are shown in Table 3:

[0132] Table 3

[0133] Compared to polyurethane material B and the fiber mesh produced by electrospinning, the fiber mesh produced by coaxial electrospinning uses a stronger, high-molecular-weight polyethylene material for the inner layer, further enhancing the mechanical strength of the composite membrane. Furthermore, the outer layer uses a polyurethane material that better blends with the matrix, resulting in better compatibility between the fibers and the matrix material, reducing stress concentration at the interface. Test results show that the composite membrane produced by coaxial electrospinning exhibits superior mechanical strength and edge tear resistance.

[0134] Example 4

[0135] (1) High temperature resistant polyurethane A (melting point 195°C, Shore hardness 80D, same as Example 1) THF / V DMF The mixture was stirred for 4 h in a 1:1) solution to prepare a 10% (wt.%) uniform solution, which was a polyurethane A solution.

[0136] (2) The obtained polyurethane A solution was electrospun under the conditions of humidity of 50%, voltage of 15 kV, propulsion speed of 1 mL / h, spinning distance of 20 cm and needle type of 21G to obtain a prefabricated membrane with a thickness of 0.8 to 1 mm.

[0137] (3) The prefabricated membrane was vacuum dried at room temperature for 48 h to remove the residual solvent.

[0138] (4) The preformed film treated in step (3) is placed in a hot pressing mold containing polyurethane B particles (melting point 160° C., Shore hardness 80A, polyurethane B particles are the same as in Example 1, and the mass ratio of preformed film to polyurethane B particles is 1:1). The hot pressing mold is heated at a temperature of 170° C. for 10 minutes until the polyurethane B particles are completely melted but the preformed film is not melted. The melted polyurethane B fully infiltrates the preformed film.

[0139] (5) Molding to form a polymer film with a reinforced mesh structure in the middle. The film thickness is 0.15-0.20mm.

[0140] According to ATSM D412 and ATSM D624, the mechanical properties of polyurethane B films (polyurethane B is formed by conventional methods, such as pouring a polyurethane B solution into a flat mold and allowing the solvent to evaporate) and composite films were measured. The test results are shown in Table 4:

[0141] Table 4

[0142] Example 5

[0143] (1) High temperature resistant polyurethane A (melting point 195°C, Shore hardness 80D, same as Example 1) THF / V DMF The mixture was stirred for 4 h in a 10% (wt.%) uniform solution, which was a polyurethane A solution.

[0144] (2) The obtained polyurethane A solution was electrospun under the conditions of humidity of 50%, voltage of 15 kV, propulsion speed of 1 mL / h, spinning distance of 20 cm and needle type of 21G to obtain a prefabricated membrane with a thickness of 0.8 to 1 mm.

[0145] (3) The prefabricated membrane was vacuum dried at room temperature for 48 h to remove the residual solvent.

[0146] (4) The preformed film treated in step (3) is placed in a hot pressing mold containing polyurethane B particles (melting point 160° C., Shore hardness 80A, polyurethane B particles are the same as in Example 1, and the mass ratio of preformed film to polyurethane B particles is 1:1). The hot pressing mold is heated at a temperature of 170° C. for 10 minutes until the polyurethane B particles are completely melted but the preformed film is not melted. The melted polyurethane B fully infiltrates the preformed film.

[0147] (5) Molding to form a polymer film with a reinforced mesh structure in the middle. The film thickness is 0.15-0.20mm.

[0148] (6) The composite film obtained in step (5) is placed in a plasma discharge machine, SO2 is used as the reaction gas, the power is 200W, and the treatment is carried out for 10 minutes to obtain a plasma-treated polymer film.

[0149] The LDH content released by the platelets adsorbed on the material was measured to detect the adhesion of the material to platelets.

[0150] Specific experimental process:

[0151] (1) After the sample membrane was exposed to fresh platelet-rich plasma at 37°C for 30 minutes, the membrane was carefully washed with PBS. (2) After air drying, 150 μL of LDH release reagent diluted 10 times with PBS was added to the well plate and the 96-well plate was shaken to mix evenly. Then, the plate was placed in a 37°C incubator for 1 hour. (3) 120 μL of supernatant from each well was taken and added to a new 96-well plate. Then, three solutions (lactic acid solution, enzyme solution, and 1X INT solution) were added in a 1:1:1 ratio to prepare the detection solution. 60 μL of detection solution was added to the supernatant of each well, mixed evenly, and incubated on a horizontal shaker at room temperature in the dark for 20-30 minutes. The absorbance of the solution at 490 nm was then measured using an enzyme reader. The test results are shown in Figure 6. The surface-treated polymer membrane has good anti-platelet adhesion.

[0152] The contact angle between water and the sample was measured using an SZ10-JC2000C contact angle meter. The test results are shown in Figure 7, indicating that the surface-treated polymer film has a small contact angle and good hydrophilicity.

[0153] The above-described embodiments merely represent several implementation methods of the present application. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art could make various modifications and improvements without departing from the spirit of the present application, all of which fall within the scope of protection of the present application. Therefore, the scope of protection of the present patent application shall be determined by the appended claims.

Claims

1. A polymer valve material, characterized in that: include: The skeleton is formed by electrospinning using polyurethane A as a raw material; The composite layer uses polyurethane B as a raw material and is composited onto the skeleton.

2. The polymer valve material according to claim 1, characterized in that The melting point of polyurethane A is higher than the melting point of polyurethane B and the difference is at least 30°C.

3. The polymer valve material according to claim 2, characterized in that: The melting point of the polyurethane A is 180-300°C, and the melting point of the polyurethane B is 100-240°C.

4. The polymer valve material according to claim 1, wherein The melting point of the polyurethane A is 180-300° C.; the Shore hardness of the polyurethane A is 50D-90D.

5. The polymer valve material according to claim 1, characterized in that: The melting point of the polyurethane B is 100-240° C.; the Shore hardness of the polyurethane B is 50A-80A.

6. The polymer valve material according to claim 1, characterized in that The thickness of the skeleton is 0.1 mm to 1 mm.

7. The polymer valve material according to claim 1, characterized in that: The porosity of the skeleton is 65% to 90%.

8. The polymer valve material according to claim 1, characterized in that: The thickness of the composite layer is 0.05 mm to 0.5 mm.

9. The polymer valve material according to claim 1, characterized in that: The raw materials for forming the skeleton by electrospinning also include core material raw materials, and the core material raw materials and the polyurethane A are coaxially electrospun to form the skeleton.

10. The polymer valve material according to claim 9, characterized in that: The polyurethane A is wrapped around the core material, and the strength of the core material raw material is higher than that of the polyurethane A.

11. The polymer valve material according to claim 9, characterized in that: The core material is made of polyamide PA or polyethylene PE.

12. A method for preparing a polymer valve material, characterized in that: include: Spinning step, electrospinning the polyurethane A solution to obtain a prefabricated membrane; a compounding step of compounding polyurethane B with the prefabricated film to obtain the polymer valve material; The adjustment step is to perform a hot pressing treatment on the prefabricated membrane before or during the compounding process.

13. The method for preparing a polymer valve material according to claim 12, wherein: In the spinning step, the polyurethane A solution and the core material solution are coaxially electrospun to obtain a prefabricated membrane; The core material solution is a polyamide PA solution or a polyethylene PE solution.

14. The method for preparing a polymer valve material according to claim 13, wherein: The ratio of the core material solution to the polyurethane A solution is calculated based on the mass ratio of the core material PA or PE to the polyurethane A being 5:1 to 1:

5.

15. The method for preparing a polymer valve material according to claim 13, wherein: The thickness of the prefabricated membrane is 0.1-1 mm.

16. The method for preparing a polymer valve material according to claim 13, wherein: The porosity of the prefabricated membrane is 65% to 90%.

17. The method for preparing a polymer valve material according to claim 13, wherein: The adjustment step is to perform a hot pressing treatment on the prefabricated membrane before the compounding step, and then dip-coating the prefabricated membrane in a polyurethane B solution or a polyurethane B prepolymer solution during compounding after the hot pressing treatment.

18. The method for preparing a polymer valve material according to claim 17, wherein: During the dip coating, the prefabricated membrane after the heat pressing treatment is immersed in the polyurethane B solution for 4 to 60 seconds and then taken out.

19. The method for preparing a polymer valve material according to claim 18, wherein: The mass percentage concentration of the polyurethane B solution is 20% to 30%.

20. The method for preparing a polymer valve material according to claim 17, wherein: During dip coating, the solvent in the polyurethane B solution or the polyurethane B prepolymer solution is DMF or DMAc.

21. The method for preparing a polymer valve material according to claim 17, wherein: When dipping in polyurethane B prepolymer, the polymer diol and isocyanate are first prepolymerized; After the prepolymerization reaction is completed, a diol small molecule chain extender is added to obtain a polyurethane B prepolymer; The prefabricated membrane after the heat pressing treatment is then immersed in the polyurethane B prepolymer and a chain extension reaction is carried out under heating conditions.

22. The method for preparing a polymer valve material according to claim 13, wherein: The adjustment step is to perform hot pressing during the compounding process, including placing the prefabricated film and polyurethane B particles in a hot pressing mold, heating the hot pressing mold to melt the polyurethane B particles while the prefabricated film is not melted, and allowing the melted polyurethane B to infiltrate the prefabricated film.

23. The method for preparing a polymer valve material according to claim 22, wherein: The mass ratio of the prefabricated film to polyurethane B is 1:3 to 3:

1.

24. The method for preparing a polymer valve material according to claim 22, wherein: The temperature of the hot pressing treatment is 100 to 240° C., and the time of the hot pressing treatment is 5 minutes to 2 hours.

25. The method for preparing a polymer valve material according to claim 13, wherein: Also includes: The polymer valve material obtained in the compounding step is subjected to plasma treatment.

26. The method for preparing a polymer valve material according to claim 25, wherein: The conditions of the plasma treatment are: using SO2, CO2, NH3 or O2 as the reaction gas, the power is 100-250W, and the treatment time is 5-15 minutes.

27. A polymer valve material, characterized in that: Prepared by the preparation method according to any one of claims 12 to 26.

28. An artificial heart valve, characterized in that: It comprises a stent and a valve material sewn on the stent, wherein the valve material is the polymer valve material according to any one of claims 1 to 11 or claim 27.